2017
DOI: 10.1037/hea0000544
|View full text |Cite
|
Sign up to set email alerts
|

The role of a palliative care intervention in moderating the relationship between depression and survival among individuals with advanced cancer.

Abstract: Objective Randomized controlled trials (RCTs) of early palliative care interventions in advanced cancer have positively impacted patient survival, yet the mechanisms remain unknown. This secondary analysis of two RCTs assessed whether an early palliative care intervention moderates the relationship between depressive symptoms and survival. Methods The relationships among mood, survival, and early palliative care intervention were studied among 529 advanced cancer patients who participated in two RCTs. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…This came in accordance with Prescott et al, (2017) who reported that patients with advanced cancer who also have depressive symptoms benefit the most from early palliative care. Also Rosenstein, (2011) reported that the pharmacotherapy of depression in patients with advanced cancer should be guided by a palliative care approach focused on symptom reduction, irrespective of whether the patient meets diagnostic criteria for major depression.…”
Section: Discussionsupporting
confidence: 91%
“…This came in accordance with Prescott et al, (2017) who reported that patients with advanced cancer who also have depressive symptoms benefit the most from early palliative care. Also Rosenstein, (2011) reported that the pharmacotherapy of depression in patients with advanced cancer should be guided by a palliative care approach focused on symptom reduction, irrespective of whether the patient meets diagnostic criteria for major depression.…”
Section: Discussionsupporting
confidence: 91%
“…This already high cancer incidence is accompanied by the even higher risk in Latinos of experiencing elevated levels of depressive symptoms, emotional distress, and reduced quality of life when compared to other minority ethnic groups [3,4]. Further, per our recent systematic review, a lack of participation of Latinos, including Puerto Ricans, on the development of psychosocial intervention was found [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Puerto Rican Cancer Patientsmentioning
confidence: 73%
“…The evidence base continued to expand beyond these seminal studies and demonstrated positive effects on illness communication, adaptive coping, prognostic awareness, treatment decision making, end‐of‐life care, caregiver outcomes, and cost‐effectiveness . As the science matured, palliative care researchers were able to identify mediators and moderators of the beneficial effects of palliative care …”
Section: Strategy 1: Stimulating the Science In Specific Gap Areasmentioning
confidence: 99%
“…65 As the science matured, palliative care researchers were able to identify mediators and moderators of the beneficial effects of palliative care. 59,[66][67][68] By 2016, the evidence base had grown enough to allow meta-analyses to be conducted on palliative care clinical trials. First, Kavalieratos et al 69 evaluated 43 studies that tested at least 2 domains of palliative care (eg, depression and quality of life).…”
Section: The Sciencementioning
confidence: 99%